Maximising the chances for positive impacts of fisheries and aquaculture Official Development Assistance. (September 2019) - Macfadyen, Graeme; Huntington, Tim; Cappell, Rod
Abstract: This short communication provides some reflections based on experience gained of designing, implementing and evaluating Official Development Assistance (ODA) in the fisheries and aquaculture sector. It highlights the importance of the 'human' elements in project design, implementation, and evaluation. It argues that while external factors and technical issues may be strong determinants of success or failure, more important is the 'human element' in terms of the skills, needs, motivations and aspirations of project designers, implementers, evaluators, and beneficiaries.